Divergent mitochondrial respiratory chains in phototrophic relatives of apicomplexan parasites - Flegontov, Pavel; Michálek, Jan; Janouškovec, Jan; Lai, De-Hua; Jirků, Milan; Hajdušková, Eva; Tomčala, Aleš; Otto, Thomas D; Keeling, Patrick J; Pain, Arnab; Oborník, Miroslav; Lukeš, Julius (Molecular biology and evolution, 2015)
Four respiratory complexes and ATP-synthase represent central functional units in mitochondria. In some mitochondria and derived anaerobic organelles, a few or all of these respiratory complexes have been lost during evolution. We show that the respiratory chain of Chromera velia, a phototrophic relative of parasitic apicomplexans, lacks complexes I and III, making it a uniquely reduced aerobic mitochondrion. In Chromera, putative lactate:cytochrome c oxidoreductases are predicted to transfer electrons from lactate to cytochrome c, rendering complex III unnecessary. The mitochondrial genome of Chromera has the smallest known protein-coding capacity of all mitochondria, encoding just cox1 and cox3 on heterogeneous linear molecules. In contrast, another photosynthetic relative of apicomplexans, Vitrella brassicaformis, retains the same set of genes as apicomplexans and dinoflagellates (cox1, cox3, and cob).
Keywords: respirační komplex I; Lactic Acid; Mitochondria; Apicomplexa; fotosyntéza; cytochromy c; genetická variace; fylogeneze; Photosynthesis; Phylogeny; transport elektronů; molekulární evoluce; paraziti; Evolution, Molecular; Mitochondrial Proton-Translocating ATPases; Chromera; genom mitochondriální; Electron Transport; Genome, Mitochondrial; mitochondriální protonové ATPasy; kyselina mléčná; Animals; evolution; zvířata; respiratory chain; Cytochromes c; Alveolata; anaerobic metabolism; Electron Transport Complex I; Vitrella; Genetic Variation; Parasites; mitochondrie